Sources of Work Stress of English Language Teachers in Secondary Government Schools - Harahap, Aziddin; Siregar, Sakinah Ubudiyah; Purnama, Iwan (Journal La Edusci, 2025)
This study aims to analyze the implementation of regional education policies to improve the understanding of the Qur'an in public elementary schools in South Labuhanbatu Regency. This policy is based on Regional Regulation No. 10 of 2015 concerning Improving Understanding of the Holy Book. The study used a naturalistic qualitative approach with interview, observation, and documentation study techniques. The results show that the Qur'an-based education policy is implemented through several main strategies: teacher recruitment based on religious competency, intensive training, the preparation of a standard syllabus, annual work contracts, and the implementation of Qur'an learning outside of main school hours. The success of this program is supported by the synergy between the local government, the Education Office, the Ministry of Religious Affairs, schools, and the community. The analysis shows that this policy is aligned with the principles of strategic management, transformational leadership, and systems theory, despite limitations in funding and teacher capacity. The implications of this study emphasize the importance of regional education policies as a model for improving Qur'an literacy in public elementary schools.